1996
DOI: 10.1128/mcb.16.8.4273
|View full text |Cite
|
Sign up to set email alerts
|

Signals from the Stressed Endoplasmic Reticulum Induce C/EBP-Homologous Protein (CHOP/GADD153)

Abstract: The gene encoding C/EBP-homologous protein (CHOP), also known as growth arrest and DNA-damageinducible gene 153 (GADD153), is activated by agents that adversely affect the function of the endoplasmic reticulum (ER). Because of the pleiotropic effects of such agents on other cellular processes, the role of ER stress in inducing CHOP gene expression has remained unclear. We find that cells with conditional (temperature-sensitive) defects in protein glycosylation (CHO K12 and BHK tsBN7) induce CHOP when cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
479
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 629 publications
(503 citation statements)
references
References 47 publications
(55 reference statements)
20
479
0
2
Order By: Relevance
“…23,27,28,56,57. Overexpression of BiP attenuates the induction of CHOP in ER stress and reduces ER stressinduced apoptosis. 31 CHOP À/À mice exhibit reduced apoptosis in response to ER stress. 56,58,59 Thus, CHOP plays an important role in ER stress-induced apoptosis.…”
Section: Downstream Of Chop In Er Stress-induced Apoptosismentioning
confidence: 98%
See 1 more Smart Citation
“…23,27,28,56,57. Overexpression of BiP attenuates the induction of CHOP in ER stress and reduces ER stressinduced apoptosis. 31 CHOP À/À mice exhibit reduced apoptosis in response to ER stress. 56,58,59 Thus, CHOP plays an important role in ER stress-induced apoptosis.…”
Section: Downstream Of Chop In Er Stress-induced Apoptosismentioning
confidence: 98%
“…Subsequent studies revealed that a DNAdamaging nucleoside analogue or UV light alone does not induce CHOP. 31 Glucose deprivation is known to induce ER stress, presumably by inhibiting N-linked protein glycosylation Figure 1 Proposed profile of ER stress response. In an early phase, translational attenuation occurs to reduce the load of ER.…”
Section: Expression Profile Of Chopmentioning
confidence: 99%
“…The key players of the unfolded protein response (UPR) are three chronologically activated ER resident signaling proteins: protein kinaselike ER-resident kinase (PERK), inositol requiring 1 (Ire1) and activating transcription factor-6(ATF-6) [3][4][5][6]. Several pro-apoptotic factors and signaling pathways, including C/EBP homologous protein/growth arrest and DNA damage-inducible gene 153 (CHOP/GADD153), pro-apoptotic Bcl-2 family members, and caspase-12, have been shown to be involved in ER stress-induced cell death [7][8][9]. CHOP is a key pro-apoptotic transcription factor induced during ER stress [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…CHOP is a member of the CCAAT/enhancer binding protein (C/EBP) family of transcription factors (reviewed in Ron and Habener, 1992;Leckstrom-Himes and Xanthopoulos, 1998;Ramji and Foka, 2002) and is ubiquitously expressed at low levels in proliferating cells, but strikingly upregulated by oxidative stress, endoplasmatic reticulum (ER) stress and DNA damage in different adult tissues (Ubeda et al, 1996;Wang et al, 1996;Talukder et al, 2002). CHOP induces cell cycle arrest and apoptosis in response to cellular stress factors (Zinszner et al, 1998;Maytin et al, 2001), and was therefore also termed 'growth arrest and DNA damageinducible gene' (GADD153).…”
Section: Introductionmentioning
confidence: 99%